2017
DOI: 10.1002/jcu.22558
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the inferior vena cava presenting as a cardiac mass

Abstract: Primary tumors of the inferior vena cava (IVC) are rare. The most common primary malignancy is leiomyosarcoma (LMS), with a severe prognosis. Right-atrium (RA) involvement is seen in about 20 percent of cases. We report the case of a 53-year-old woman admitted to the intensive care unit because of progressive dyspnea with lower limb edema. Echocardiography demonstrated a large mass in the RA. At open-heart surgery, the tumor appeared located in the IVC infrahepatic segment, completely obstructing the lumen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…11,12 IHC makers frequently reported positive were smooth muscle actin, desmin, vimentin, and caldesmon. 13,49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 IHC makers frequently reported positive were smooth muscle actin, desmin, vimentin, and caldesmon. 13,49…”
Section: Resultsmentioning
confidence: 99%
“…11,12 IHC makers frequently reported positive were smooth muscle actin, desmin, vimentin, and caldesmon. 13,49 Management Surgery. Most patients (n = 81) underwent upfront resection (88.0%), while four others were operated following neoadjuvant treatment (Table 2).…”
Section: Clinical Features and Diagnostic Modalities (Imaging And Tis...mentioning
confidence: 99%
“…The largest case series by Perhavec et al showed the most common reasons for technical unresectability to be the involvement of the superior mesenteric vessels, followed by the involvement of bone, portal vein, or hepatic axis (8). When managing an intracardiac tumor thrombus, wide resection is still preferred and intra-operative cardiopulmonary bypass should be considered to facilitate resection and maintain organ perfusion (20)(21)(22) Their rarity poses a great oncologic and surgical challenge, as the bene ts of systemic treatment are unde ned, and surgical management remains controversial. Neoadjuvant therapy can be used to reduce tumor size and improve resectability.…”
Section: Discussionmentioning
confidence: 99%
“…La radioterapia y la quimioterapia adyuvantes han demostrado prolongar la supervivencia y mejorar el control de la enfermedad en algunos casos 19,20 . La doxorrubicina, la ifosfamida, la vincristina, el etopósido, el uracilo, el cisplatino, la ciclofosfamida y la mitomicina se encuentran entre los agentes quimioterapéuticos que se han probado, con resultados muy variados 10,21,22 . Los factores que determinan la supervivencia incluyen el índice mitótico del tumor, la presencia de metástasis, la necrosis en la sección del tumor y la localización del tumor en el lado izquierdo del corazón 20 .…”
Section: Discussionunclassified